Facts and Fears in Public Reporting: Patients' Information Needs and Priorities When Selecting a Hospital for Cancer Care. (August 2019) - Chimonas, Susan; Fortier, Elizabeth; Li, Diane G.; Lipitz-Snyderman, Allison
Objective. Public reporting on the quality of provider care has the potential to empower patients to make evidence-based decisions. Yet patients seldom consult resources such as provider report cards in part because they perceive the information as irrelevant. To inform more effective public reporting, we investigated patients' information priorities when selecting a hospital for cancer treatment. We hypothesized that patients would be most interested in data on clinical outcomes.Methods. An experienced moderator led a series of focus groups using a semistructured discussion guide. Separate sessions were held with patients aged 18 to 54 years and those older than 54 years in Philadelphia, Pennsylvania; Phoenix, Arizona; and Indianapolis, Indiana, in 2017. All 38 participants had received treatment for cancer within the past 2 years and had a choice of hospitals.Results. In selecting hospitals for cancer treatment, many participants reported that they considered factors such as reputation, quality of the facilities, and experiences of other patients. For most, however, decisions were guided by trusted advisors, with the majority agreeing that a physician's opinion would sway them to disregard objective data about hospital quality. Nonetheless, nearly all expressed interest in having comparative data. Participants varied in selecting from a hypothetical list, "the top 3 things you would want to know when choosing a hospital for cancer care." The most commonly preferred items were overall care quality, timeliness, and patient satisfaction. Contrary to our hypothesis, many preferred to avoid viewing comparative clinical outcomes, particularly survival.Conclusions. Patients' information preferences are diverse. Fear or other emotional responses might deter patients from viewing outcomes data such as survival. Additional research should explore optimal ways to help patients incorporate comparative data on the components of quality they value into decision making.